ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PENERIMAAN ASLI DAERAH KOTA BONTANG TAHUN 2012-2014 - AMALIA PUSPITASARI, DIANA Amalia (Jurnal Akuntansi AKUNESA, 2014)
The Indonesian Government has reformed in taxation known as Autonomous Territory which is dividing resources of revenue such as territorial taxes and central taxes. Hotel and restaurant taxes is one of the City/Regencial taxes which are having an enormous potential in Bontang City, where big companies at and they need public services such as hotels and restaurants to keep their employees on the line. The purpose of this research is to know how the effectivity and the contribution of amount of hotel and restaurant taxes for the Native Territorial Revenue in Bontang City. This research did in Revenues Departement, Monetary Management, and Territorial Assests of Bontang City. This research used qualitative method, by analyzing target data, realization of revenue and contribution of hotel and restaurant taxes for 2012-2014 period. The result show that every target period and realization of hotel and restaurant taxes revenue are increasing with average effectivity level at 138,64% which means very good. And so with the contribution that shows an average score at 6,07% which means contribution of parking taxes toward Native Territorial Revenue is still very less.Keywords: Autonomous Territory, Territorial Taxes, Central Taxes, Hotel Taxes, Restaurant Taxes, Effectivity, Contribution.